2018
DOI: 10.1136/vetreco-2018-000298
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methadone and acepromazine premedication on tear production in dogs

Abstract: ObjectivesTo evaluate the combined effect of intramuscular acepromazine and methadone on tear production in dogs undergoing general anaesthesia for elective, non-ocular procedures.DesignProspective, non-randomised, pre-post treatment study.SettingPatients were recruited from a referral practice in the UK.MethodsThirty client-owned dogs were enrolled in this study and received a combined intramuscular premedication of methadone (0.3 mg/kg) and acepromazine (0.02 mg/kg) before general anaesthesia for elective, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…The association of a sedative drug with a full µ-opioid agonist resulted in a marked decrease in tear production, suggesting an additional effect in reducing the STT 1 readings, as previously observed by Volk et al [18], who tested the combination of the two drugs administered at the same time in the same syringe. The simultaneous inoculation of methadone may maintain the down regulation of tear production by acepromazine, due to its sedative effect that can persist until 4-6 h. Some authors reported that the synergism between acepromazine and methadone provides more profound sedation in dogs than either drug administered individually, with an early onset of action and a longer effect [14].…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…The association of a sedative drug with a full µ-opioid agonist resulted in a marked decrease in tear production, suggesting an additional effect in reducing the STT 1 readings, as previously observed by Volk et al [18], who tested the combination of the two drugs administered at the same time in the same syringe. The simultaneous inoculation of methadone may maintain the down regulation of tear production by acepromazine, due to its sedative effect that can persist until 4-6 h. Some authors reported that the synergism between acepromazine and methadone provides more profound sedation in dogs than either drug administered individually, with an early onset of action and a longer effect [14].…”
Section: Discussionsupporting
confidence: 71%
“…Many authors have reported that tear production in dogs is affected by tranquilizers, sedatives, opioids and general anesthetic drugs [ 2 , 3 , 4 , 8 , 16 ], although a variable effect on canine tear production was reported due to the inoculation of full μ-opioid receptor agonists, either alone or in association with sedatives or tranquilizers [ 2 , 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main cause is the suppression of parasympathetic innervation of the lacrimal gland, as demonstrated in rats and rabbits experimentally para-sympathectomized by sectioning of the greater superficial petrosal nerve [ 9 , 10 , 11 ]. A marked decrease in tear production after induction of anesthesia has been reported in humans [ 12 , 13 , 14 , 15 ] and in dogs, using different anesthetic and sedative protocols [ 16 , 17 , 18 , 19 , 20 , 21 ]. The loss of corneal integrity resulting from perioperative dry eye can lead to corneal abrasions, which are the most common ocular complication in humans during general anesthesia for non-ophthalmic surgery [ 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%